Asbestos – identification on bulk materials - Proença, Maria do Carmo (2017)
Asbestos is the generic term for various types of natural silicates of magnesium and / or iron, which have fibrous forms. Due to its properties, asbestos has been widely used in industry, it is estimated that is present in approximately three thousand different products. It is currently known that asbestos causes, various types of diseases in exposed human beings, such as asbestosis, lung cancer and mesothelioma (cancer of the pleura or peritoneum). Although the use of asbestos is already prohibited, its extended use in the past, requires the adequate surveillance in places where it is applied in order to reduce as much as possible the risk of exposure to this agent. The Air and Occupational Health Unit of the National Institute of Health Doutor. Ricardo Jorge (INSA) identifies since 1985, the presence of asbestos fibers in materials, using the Polarised Light Microscopy, method 9002 of NIOSH, Manual of analytical methods, fourth edition. Since its ban in 2005, by the Community Directive 2003/18/EC, requests for such assessments have risen considerably (about 300%) mainly in the assessment of air surveillance in schools. Requests for asbestos identification in materials, had a very significant increase since 2014, when the government undertook to carry out a survey of “materials suspected of containing asbestos” (MCA) in buildings, facilities and public facilities provided for in Law No. 2/2011 but, to date, it had not yet been made. This study aims to make the evaluation of the results for all material samples analyzed in INSA since 2012, with regard to asbestos detection. Conclusions from that study demonstrate that in 75% of the analyzed materials was not detected the presence of asbestos. The majority (84%) of materials where the presence of asbestos fibers was detected corresponds to asbestos cement sheets containing asbestos chrysotile type and in older cement sheets asbestos chrysotile and crocidolite type in accordance with the expectable.